Rocking at 81 and Rolling at 34: ROC Cut-Off Scores for the Negative Acts Questionnaire–Revised in Serbia - Petrović, Ivana B.; Vukelić, Milica; Čizmić, Svetlana (Frontiers in Psychology, 2017)
Researchers are still searching for the ways to identify different categories of employees according to their exposure to negative acts and psychological experience of workplace bullying. We followed Notelaers and Einarsen’s application of the ROC analysis to determine the NAQ-R cut-off scores applying a “lower” and “higher” threshold. The main goal of this research was to develop and test different gold standards in determining the NAQ-R cut-off scores by introducing both personally and organizationally relevant criteria. Apart from combining self-labeling as a victim with self-perceived health, we also tested the gold standards developed as a combination of self-labeling with life satisfaction, self-labeling with intention to leave as well as a complex gold standard based on self-labeling, self-perceived health, life satisfaction and intention to leave taken together. The ROC analysis on Serbian workforce data has proved the applicability of different gold standards. For identifying employees in a preliminary stage of workplace bullying, the most applicable was the gold standard based on self-labeling and intention to leave (score 34 and higher). The most accurate identification of victims could be based on the most complex gold standard (score 81 and higher). This research encourages further investigation of gold standards in different cultural settings.